Metachronous rectal metastasis from primary transverse colon cancer: a case report - Shigehiro Kojima; Tsuguo Sakamoto; Yuko Nagai; Masayuki Honda; Fumihiro Ogawa (Surgical Case Reports)
Abstract Background Colorectal metastases from primary colorectal cancers are very rare, and little is known about their epidemiological aspects or the best diagnostic and therapeutic strategies. Herein, we report a case of a 65-year-old woman with suspected metachronous metastasis to the rectum from primary transverse colon cancer. Case presentation The patient underwent a laparoscopic extended right hemicolectomy for primary transverse colon cancer. Histopathological examination showed moderately differentiated adenocarcinoma, and the tumor was diagnosed as stage IIA (T3, N0, M0). Fifteen months after her colectomy, a computed tomography scan demonstrated a rectal tumor and a right ovarian tumor. Colonoscopy revealed a superficial elevated lesion in the middle rectum, and histological analysis showed moderately differentiated adenocarcinoma. Laparoscopic low anterior resection preserving the left colic artery and bilateral adnexectomy were performed. Histological examination of the rectal tumor showed that adenocarcinoma was mainly present in the submucosa and muscularis propria, while the carcinoma-involved region of the mucosal layer had mucosal colonization representing the spread of metastatic tumor cells along the basement membrane of preexisting crypts and/or villi. The right ovarian tumor proved to be moderately differentiated adenocarcinoma that was positive for cytokeratin 20 and negative for cytokeratin 7 staining, indicating metastasis from the colorectal cancer. The rectal and ovarian tumors were similar to transverse colon cancer in architectural and cytological atypia. Both adenocarcinomas of the transverse colon and rectum were negative for p53 in immunohistochemical staining and RAS wild type in genetic assessment. These findings support a possible diagnosis of rectal and ovarian metastasis from the primary transverse colon cancer. The patient recovered well after surgery, and neither relapse nor metastasis was observed 18 months after surgery. Conclusion Distinguishing primary from metastatic colorectal cancer can be challenging, but a comprehensive evaluation of histological features, clinical history, and tumor distribution can enable making a correct diagnosis and implementing optimal treatment.